A STUDY ON THE USE OF METACOGNITIVE READING STRATEGIES IN COMPREHENDING READING TOEFL TEST MATERIALS AMONG UNIVERSITY STUDENTS - Khariyani, Sadiatul (2012)
This study is descriptive research investigating metacognitive reading strategies which are frequently used among university students in reading TOEFL test materials at English Education Program in Bandung, West Java. This study also aims to find out which metacognitive reading strategies are considered the most helpful for the students especially in answering questions in reading comprehension test successfully and the reasons why they employed those strategies. The participants of this study were third-year students of English Education Program in Bandung. The data were obtained from three sources as interviews, TAPs (Thinking-Aloud Protocols) that followed Aengpongpaow (2008) and reading journals which were conducted with 20 students; 10 high and low achieving students. The data were analyzed using instruments adapted from Metacognitive Reading Strategies Categories based on Cohen (1998) and previous study conducted by Kummin&Rahman (2010). The results of data analysis show that high and low achieving students most frequently used repetition, problem solving, using contextual clues, skimming, background knowledge, and translation. The analysis also shows that there were differences in term of frequency and the way how the students use the strategies. In addition, regarding to the research question about the most helpful metacognitive reading strategies for students especially when answering questions in reading comprehension test successfully, it was found that the students who successfully answered questions in reading comprehension test used three metacognitive reading strategies such as skimming, looking for specific purposes and using contextual clues. Finally, based on the data, it is indicated that the students employed metacognitive strategies because: (a) it is easier to understand the text, (b) it is easier to answer the questions, (c) it is easier to know the main idea of the text, and (d) it helps the students to solve their problems in reading. Considering the limited participants in this study, it is suggested to carry out further research by using large group of participants in order to have a wider perspective. Such information can help teachers to think further about what treatment should be conducted to enhance students' reading comprehension.